On the question of the activities of the government of the Mountain republic (may 1919 – мay 1919) - Natalia Anatolyevna Dobryakova (Кавказология, 2023)
The article discusses the genesis, presence, and formation of requirements for the deposition of one of the several state entities on the territory of the former Russian Empire’s Caucasian viceroyalty – the Mountain Republic. The emphasis is on the fact that the liberal mountain leaders did not set out to secede from Russia; they were quite loyal to the Provisional Government, and it was only the Bolshevik seizure of power in the country and in the North Caucasus that pushed them to the decision to establish an independent state. The Ottoman and German empires allegedly supported their decision to establish their own state, but the mountain liberals lacked the wherewithal to establish a full-fledged state. The emphasis is on the fact that the decision to fire A.-M. Chermoyev’s cabinet was made under British pressure, and that the resignation of P. Kotsev and appointment of M. Khalilov could have been prompted by the White Guards.